The Great Problems of Micro-language - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2021)
The article contains a review of Marinela Mladenova’s book Банатски български книжовен език в контекста на славянската микролингвистика. История, динамика на нормата и езикови политики, the author of which focuses on the normalization and development of the language norms of the Bulgarian minority living in Banat. The literary language of the Banat Bulgarians has the status of an island language because it has been used by the Catholic community for over two hundred years living outside their homeland, in a foreign linguistic environment. It developed its own literary norm through time, mostly under the influence of Croatian, Romanian, and Hungarian, and is now regarded a micro-language. Marinela Mladenowa’s book, as well as the accompanying article, discuss the political and societal reasons that influenced the development of this standard.